2013
DOI: 10.1016/j.neuron.2013.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Homeostatic Control of Synaptic Transmission by Distinct Glutamate Receptors

Abstract: Summary Glutamate is the most abundant excitatory neurotransmitter in the brain, and distinct classes of glutamate receptors coordinate synaptic transmission and spike generation upon various levels of neuronal activity. However, the mechanisms remain unclear. Here, we found that loss of synaptic AMPA receptors increased kainate receptor activity in cerebellar granule cells, without changing NMDA receptors. The augmentation of kainate receptor-mediated currents in the absence of AMPA receptor activity is requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 69 publications
4
33
0
Order By: Relevance
“…Because global stg/γ-7 dKO mice did not exhibit such enhancement, rather a decrease relative to WT (Fig. 1 C and D), it is possible that this enhancement reflects a homeostatic effect of the late-onset loss of cf-EPSC responses as a way of maintaining synaptic activity, previously reported in stg CGNs (26). However, γ-2 PC KO; γ-7 WT mice showed no reduction in KA responses, indicating that approximately half of control levels of excitatory cf input onto PCs is sufficient to maintain essentially normal cerebellar function.…”
Section: Discussionmentioning
confidence: 68%
“…Because global stg/γ-7 dKO mice did not exhibit such enhancement, rather a decrease relative to WT (Fig. 1 C and D), it is possible that this enhancement reflects a homeostatic effect of the late-onset loss of cf-EPSC responses as a way of maintaining synaptic activity, previously reported in stg CGNs (26). However, γ-2 PC KO; γ-7 WT mice showed no reduction in KA responses, indicating that approximately half of control levels of excitatory cf input onto PCs is sufficient to maintain essentially normal cerebellar function.…”
Section: Discussionmentioning
confidence: 68%
“…In cerebellar granule cells, the native KAR complex consists of GluK2, GluK5, and Neto2 (Yan et al, 2013). GluK2 and Neto2 are detected in the PSD fraction of both wild-type and GluK5 KO mice at similar levels (Yan et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…This restricted localization of KARs is apparent in the hippocampal stratum lucidum where mossy fiber axons projecting from dentate gyrus granule neurons form complex synapses with CA3 neurons (Castillo et al, 1997; Contractor et al, 2003; Darstein et al, 2003; Mulle et al, 1998; Petralia et al, 1994; Vignes and Collingridge, 1997). In contrast, KARs are found at all synapses in the cerebellum, where granule cells receive input from only one type of excitatory afferent, the mossy fiber (Yan et al, 2013). Mechanisms underlying these synaptic differences remain unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficiency of the knockout of the GluK5 gene has not been tested sufficiently by the developers. In fact, a recent study using GluK5 KO mice found no difference between KO and WT in electrophysiological findings and expression level of synaptic proteins (Yan et al, 2013). …”
Section: Resultsmentioning
confidence: 99%